Enhanced Formation of Methylglyoxal-Derived Advanced Glycation End Products in Arabidopsis Under Ammonium Nutrition - Borysiuk, Klaudia; Ostaszewska-Bugajska, Monika; Vaultier, Marie-Noëlle; Hasenfratz-Sauder, Marie-Paule; Szal, Bożena (Frontiers in Plant Science, 2018)
Nitrate (NO3-) and ammonium (NH4+) are prevalent nitrogen (N) sources for plants. Although NH4+ should be the preferred form of N from the energetic point of view, ammonium nutrition often exhibits adverse effects on plant physiological functions and induces an important growth-limiting stress referred as ammonium syndrome. The effective incorporation of NH4+ into amino acid structures requires high activity of the mitochondrial tricarboxylic acid cycle and the glycolytic pathway. An unavoidable consequence of glycolytic metabolism is the production of methylglyoxal (MG), which is very toxic and inhibits cell growth in all types of organisms. Here, we aimed to investigate MG metabolism in Arabidopsis thaliana plants grown on NH4+ as a sole N source. We found that changes in activities of glycolytic enzymes enhanced MG production and that markedly elevated MG levels superseded the detoxification capability of the glyoxalase pathway. Consequently, the excessive accumulation of MG was directly involved in the induction of dicarbonyl stress by introducing MG-derived advanced glycation end products (MAGEs) to proteins. The severe damage to proteins was not within the repair capacity of proteolytic enzymes. Collectively, our results suggest the impact of MG (mediated by MAGEs formation in proteins) in the contribution to NH4+ toxicity symptoms in Arabidopsis.